Pengembangan Media Video Animasi Pembelajaran Berbasis Powtoon Pada Mata Pelajaran Geografi Materi Mitigasi Bencana Alam - Usep Hidayat; Fitryane Lihawa; Rusiyah Rusiyah (JAMBURA GEO EDUCATION JOURNAL, 2023)
This study aims to develop Powtoon-based learning animation video media in geography subjects, especially natural disaster mitigation materials. The research method is Research and development (RD). Data collection methods are observation, interviews, questionnaires, and documentation. The instrument used is a questionnaire. The validation of the developed media product was carried out through three stages: expert validation, limited trial, and general trial. Expert validation was carried out by media experts, materials experts, and geography teachers. The limited trial was conducted on 26 class XI students at SMA Negeri 1 Suwawa Timur totaling 26 people. The general trial was conducted on 133 students in Tapa High School and Suwawa High School, Bone Bolango Regency. The results of the material expert validation obtained a value of 78.18%, with the level of validity being included in a very valid qualification. The results of the validation by media experts obtained a value of 90%, with the level of validity being included in a very valid qualification. The results of the validation by the geography teacher obtained a value of 90% with the validity level of entering a very valid qualification. The results of the limited trial obtained a value of 90.96% (valid). The results of the general scale trial obtained a value of 91.48% (valid). Thus, Powtoon-based learning animation video media on geography subjects and natural disaster mitigation materials can be used as learning media in schools and get a very good response from students.